Analysis of the Settlement of South China Sea Disputes by the International Arbitration Tribunal - Vivi Heniasy; Delycia Anwar Rannu; Audrey Bilbina Putri (Asian Journal of Social and Humanities, 2023)
The settlement of South China Sea disputes by the International Arbitration Board is a complex challenge. The South China Sea is a strategic area disputed by several countries in Southeast Asia. International Arbitration Bodies play an important role in handling these disputes. Arbitration proceedings began in 2013 and a decision was announced in 2016. Although the decree is legally binding, its implementation still faces political and diplomatic challenges. Cooperation between the countries involved is necessary to achieve an effective solution.